2012
DOI: 10.1016/j.adolescence.2012.06.006
|View full text |Cite
|
Sign up to set email alerts
|

“Feeling” hierarchy: The pathway from subjective social status to achievement

Abstract: The current study tested a psychosocial mediation model of the association between subjective social status (SSS) and academic achievement for youth. The sample included 430 high school students from diverse racial/ethnic and socioeconomic backgrounds. Those who perceived themselves to be at higher social status levels had higher GPAs. As predicted by the model, most of the relationship was mediated by emotional distress and study skills and habits. The lower SSS students had more depressive symptoms, which le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 33 publications
1
48
1
1
Order By: Relevance
“…The items were rated on a four-point scale (1 ¼ 'near to never' to 4 ¼ 'often') and the scale mean was used as an overall measure of emotional distress. The scale has good internal consistency with a ¼ 0.90, and previous studies indicate good reliability and construct validity (Derogatis et al, 1973;Sigfusdottir, Asgeirsdottir, Sigurdsson, & Gudjonsson, 2008;Sigfusdottir, Farkas, & Silver, 2004).…”
Section: Dependent Variablementioning
confidence: 85%
“…The items were rated on a four-point scale (1 ¼ 'near to never' to 4 ¼ 'often') and the scale mean was used as an overall measure of emotional distress. The scale has good internal consistency with a ¼ 0.90, and previous studies indicate good reliability and construct validity (Derogatis et al, 1973;Sigfusdottir, Asgeirsdottir, Sigurdsson, & Gudjonsson, 2008;Sigfusdottir, Farkas, & Silver, 2004).…”
Section: Dependent Variablementioning
confidence: 85%
“…Accordingly, Destin et al [65] found that lower school SSS among U.S. high school students is associated with lower grade point averages and that this relationship is mostly mediated by depressive feelings. So far, little research has been done on SSS and personality disorders.…”
Section: Mental Healthmentioning
confidence: 96%
“…Adolescents’ SSS may also play an important role in predicting key mediators of educational outcomes, as lower feelings of SSS have been associated with increased depressive symptoms and, in turn, lower academic achievement (Destin, Richman, Varner, & Mandara, 2012). The authors describe these types of downstream effects of SSS on educational performance as a way in which adolescents may “feel” the hierarchy within their settings.…”
Section: Is It All Relative? How Do Children Perceive Their Social Stmentioning
confidence: 99%